2022
DOI: 10.1128/spectrum.00945-22
|View full text |Cite
|
Sign up to set email alerts
|

Four Novel Leaderless Bacteriocins, Bacin A1, A2, A3, and A4 Exhibit Potent Antimicrobial and Antibiofilm Activities against Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a major human pathogen that is difficult to treat because of its resistance to several widely used antibiotics. The present study aimed to identify novel anti-MRSA bacteriocins in a prominent producer of bacteriocins, Bacillus cereus group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…A lack of activity against P. aeruginosa and S. enterica was expected given Gram-negative species are typically resistant to bacteriocins due to their reduced cell wall permeability [3]. Inactivity against these two organisms is consistent with leaderless bacteriocins produced by other Bacillus species that have been shown to be bactericidal via inducing bacterial membrane damage [32][33][34]. Given their comparable antimicrobial spectra, bawcin may exhibit antimicrobial activity through a similar mechanism.…”
Section: Antimicrobial Activity Of Bawcinmentioning
confidence: 87%
“…A lack of activity against P. aeruginosa and S. enterica was expected given Gram-negative species are typically resistant to bacteriocins due to their reduced cell wall permeability [3]. Inactivity against these two organisms is consistent with leaderless bacteriocins produced by other Bacillus species that have been shown to be bactericidal via inducing bacterial membrane damage [32][33][34]. Given their comparable antimicrobial spectra, bawcin may exhibit antimicrobial activity through a similar mechanism.…”
Section: Antimicrobial Activity Of Bawcinmentioning
confidence: 87%
“…The bacterial strain Bacillus sp. TL12, isolated from soil by Liu et al, produces the antibiofilm‐active bacteriocin bacin A2 69 . Additionally, bacteriocins from soil sources are also produced by non‐ Bacillus species, such as Stenocins produced by Stenotrophomonas , ST110LD produced by Leuconostoc citreum ST110LD and BAC‐IB17 produced by S. aureus 70–72 …”
Section: Sources Of Natural Bacteriocin Isolates and Preparation Meth...mentioning
confidence: 99%
“…To illustrate, Bacin A2, identified in Bacillus sphaericus TL12, could compromise the membrane integrity of S. aureus and methicillin-resistant S. aureus biofilms, resulting in disassembling of the biofilm. [32] Similarly, it was found that the novel bacteriocin AMYX6 and XJS01 could impair the membrane integrity and consequently inhibit biofilm formation in Salmonella Enteritidis and S. aureus respectively. [33,34] The antibiofilm mechanism of action of AMPs, however, is possibly ambiguous.…”
Section: Destruction Of Mature Biofilmsmentioning
confidence: 99%